The New Features of Landslide Relief Discovered Using Lidar – Case Study from Babia Góra Massif, Western Carpathian Mountains - Łajczak, Adam; Czajka, Barbara; Kaczka, Ryszard J. (Quaestiones Geographicae, 2014)
Basing on LiDAR data, the re-interpretation of the limit and distribution of the selected landslide forms in 9 test areas were carried out. The forms are located at the slopes of the monoclinal ridge of Babia Góra Mt. (1,725 m a.s.l.) in the flysch Western Carpathians. The earlier knowledge on these landforms is shown in the unpublished map at the scale of 1:5,000 which was prepared basing on geomorphological mapping. Basing on the newest information source, subtle geomorphic signatures of landslides were found, the dynamics of these forms and directions of their further development were determined. Local differentiation of deep-seated landslides was indicated according to the relation between the sandstone layer dip and slope inclination, slope length, and altitude of the location of headwaters. An attention was paid to polycyclic relief of the highest located landslide forms, which contain the elements of glacial and nival morphology, and some are modelled by debris flows.